2013
DOI: 10.1534/genetics.113.152330
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of a Critical Regulator for Preharvest Sprouting in Wheat

Abstract: Sprouting of grains in mature spikes before harvest is a major problem in wheat (Triticum aestivum) production worldwide. We cloned and characterized a gene underlying a wheat quantitative trait locus (QTL) on the short arm of chromosome 3A for preharvest sprouting (PHS) resistance in white wheat using comparative mapping and map-based cloning. This gene, designated TaPHS1, is a wheat homolog of a MOTHER OF FLOWERING TIME (TaMFT)-like gene. RNA interference-mediated knockdown of the gene confirmed that TaPHS1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
142
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(153 citation statements)
references
References 41 publications
4
142
1
3
Order By: Relevance
“…The 3A chromosome was previously associated with a pre-harvest sprouting resistance QTL ), Qphs.pseru-3AS, reported by Liu et al (2008) and Liu and Bai (2010), although maps could not be cross-referenced. Liu et al (2013) cloned a gene from white-seeded wheat which they designated TaPHS1. Another gene on chromosome 3A reported to be involved in controlling seed dormancy and germination is TaMFT-A1, a homoeologue of MOTHER OF FT (Nakamura et al 2011;Lei et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3A chromosome was previously associated with a pre-harvest sprouting resistance QTL ), Qphs.pseru-3AS, reported by Liu et al (2008) and Liu and Bai (2010), although maps could not be cross-referenced. Liu et al (2013) cloned a gene from white-seeded wheat which they designated TaPHS1. Another gene on chromosome 3A reported to be involved in controlling seed dormancy and germination is TaMFT-A1, a homoeologue of MOTHER OF FT (Nakamura et al 2011;Lei et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in wheat, these MFT homologs (TaMFT) colocalized with the seed dormancy QTL QPhs.ocs-3A.1 on chromosome 3A (Mori et al 2005). In a subsequent study, Liu et al (2013) cloned the gene TaPHS1 underlying the QTL Qphs.pseru-3AS on the short arm of chromosome 3A in white-seeded wheat using comparative and map-based cloning approaches. They discovered two single nucleotide polymorphisms (SNPs) in the promoter region and three SNPs in the TaPHS1 gene that altered pre-harvest sprouting resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Reducing seed coat thickness led to a concurrent reduction of seed coat impermeability during legume domestication [79]. Conversely, low seed dormancy levels can reduce seed viability and trigger preharvest sprouting, causing yield losses in cereals [80]. However, this is likely to be of greater concern to modern broad-acre farmers who are locked into a single, rapid, and timely harvesting process than to early agriculturalists who had the capacity to harvest their crop in a flexible manner on repeated occasions if necessary.…”
Section: Domestication Has Left Signatures Both On Morphological As Wmentioning
confidence: 99%
“…Nakamura et al (2011) studied sequence variation in the promoter region of a wheat gene designated TaMFT, and suggested that the difference in seed dormancy between moderately and highly PHS tolerant genotypes is controlled by this dormancy gene. Liu et al (2013) using comparative mapping and map-based cloning also isolated this locus (Qphs.pseru.3As) conditioning PHS tolerance. They renamed TaMFT (of Nakamura et al 2011) to TaPHS1 to better reflect the phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al found two mutations in TaPHS1 that changed wheat from a PHS tolerant to a susceptible genotype. A GT-to-AT mutation in TaPHS1 caused mis-splicing and further led to a premature stop codon that made the transcripts from the gene nonfunctional (Liu et al 2013). Liu et al (2013) suggested selection for positive alleles at this locus would be more predictive of PHS tolerance than seed color genes.…”
Section: Introductionmentioning
confidence: 99%